2018
DOI: 10.1136/sextrans-2017-053423
|View full text |Cite
|
Sign up to set email alerts
|

Rates of pelvic inflammatory disease and ectopic pregnancy in Australia, 2009–2014: ecological analysis of hospital data

Abstract: PID and EP remain important causes of hospital admissions for female STI-associated complications. Hospital EDs care for more PID cases than inpatient departments, particularly for young women. Updated primary care data are needed to better understand PID epidemiology and healthcare usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…The result involving the association of PID with ectopic pregnancy of our study is consistent with previous studies 17, 18. Tubal damage caused by PID increases the risk of ectopic pregnancy and infertility.…”
Section: Discussionsupporting
confidence: 93%
“…The result involving the association of PID with ectopic pregnancy of our study is consistent with previous studies 17, 18. Tubal damage caused by PID increases the risk of ectopic pregnancy and infertility.…”
Section: Discussionsupporting
confidence: 93%
“…Adolescents engaging in early and unsafe sexual activities represent a high-risk population for infection with human immunodeficiency virus, other sexually transmitted diseases, and unplanned pregnancy[50]. Adolescents who experience PID are highly likely to experience adverse reproductive health outcomes [51,52]. This outcome is an important issue in the prevention of PID[5153].…”
Section: Discussionmentioning
confidence: 99%
“…As Ct can ascend to the upper genital tract, serious sequalae including PID, which can lead to ectopic pregnancy (EP) and chronic pelvic pain or infertility, are commonly observed in the Australian hospital settings. Data from the past decade (2009-2014) shows increasing Ct-related PID rates [25]. A recent study examining Ct presence in testicular biopsies showed that replicating Ct is present in human testicular tissue in up to 45% detection rates and may be associated with moderate to severe spermatogenic impairment [26].…”
Section: Sexually Transmitted Ct Infections-sti Infections With No Inmentioning
confidence: 99%